Volume 5: Turbo Expo 2003, Parts a and B 2003
DOI: 10.1115/gt2003-38256
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Numerical Studies on Heat Transfer and Aerodynamic Characteristics of Impingement Cooling Devices Combined With Pins

Abstract: This paper deals with extensive numerical studies on heat transfer characteristics and fluid dynamics inside several impingement cooling devices combined with pins. As a numerical analysis tool, a commercial software CFX-4.4, AEA Technology, is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…Quan et al [10] measured the cooling performance of an impingement system combined with pin fins by using infrared technology, and the overall cooling effectiveness was above 0.8. Funazaki et al [11,12], Son, et al [9] and Yamawaki et al [13] investigated the impingement cooling combined with circular pin fins by using transient liquid crystal technology. Their results showed that the wetted-area averaged Nusselt number of pin-fin roughened target plate was lower than flat plate; however the total heat transfer quantity of the pin-fin roughened plate increased by up to 50%, and the maximum pressure loss only increased by 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Quan et al [10] measured the cooling performance of an impingement system combined with pin fins by using infrared technology, and the overall cooling effectiveness was above 0.8. Funazaki et al [11,12], Son, et al [9] and Yamawaki et al [13] investigated the impingement cooling combined with circular pin fins by using transient liquid crystal technology. Their results showed that the wetted-area averaged Nusselt number of pin-fin roughened target plate was lower than flat plate; however the total heat transfer quantity of the pin-fin roughened plate increased by up to 50%, and the maximum pressure loss only increased by 10%.…”
Section: Introductionmentioning
confidence: 99%
“…The transient liquid crystal method [22,23] is used to measure the heat transfer characteristics on the impingement surface. Transient liquid crystal technique is Additional Impingement jets In the present work, the liquid crystal (SPN/ R30C20W) was coated on the target surface, the thermochromic liquid crystal could work in a range of 30-50 °C by undergoing red-green-blue color change.…”
Section: Experimental Methodmentioning
confidence: 99%
“…Funazaki [7][8][9] and others have done some experiments on the influence of inner duct's height on the heat transfer enhancement, and the influence of the pin height and the arrangements on heat transfer by computation. Thus, a conclusion has been drawn that pins have great importance on strengthening heat transfer for laminated plate.…”
Section: Introductionmentioning
confidence: 99%